2016
DOI: 10.1016/j.immuni.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral CD8+ T Cells Restricted by Human Leukocyte Antigen Class II Exist during Natural HIV Infection and Exhibit Clonal Expansion

Abstract: SummaryCD8+ T cell recognition of virus-infected cells is characteristically restricted by major histocompatibility complex (MHC) class I, although rare examples of MHC class II restriction have been reported in Cd4-deficient mice and a macaque SIV vaccine trial using a recombinant cytomegalovirus vector. Here, we demonstrate the presence of human leukocyte antigen (HLA) class II-restricted CD8+ T cell responses with antiviral properties in a small subset of HIV-infected individuals. In these individuals, T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…Non-classical MHC-Ib molecules are much less polymorphic than MHC-II and MHC-Ia, and typically present non-peptide antigens to semi-innate T cells, often with invariant T cell receptors, or regulate the activity of natural killer (NK) cells [1]. Although these functions are clearly the default pathways in all mammalian immune systems examined in detail, accumulating data has shown important exceptions to these general rules, in particular, the description of CD8+ T cells restricted by MHC-II [2] and MHC-E [3]. Of these observations, the most dramatic is the finding that a modified RhCMV vector strain (68-1) exclusively elicits, in Rhesus macaques, broadly targeted CD8+ T cells that are restricted by either MHC-II or MHC-E, but not MHC-Ia [4,5••].…”
Section: Introductionmentioning
confidence: 99%
“…Non-classical MHC-Ib molecules are much less polymorphic than MHC-II and MHC-Ia, and typically present non-peptide antigens to semi-innate T cells, often with invariant T cell receptors, or regulate the activity of natural killer (NK) cells [1]. Although these functions are clearly the default pathways in all mammalian immune systems examined in detail, accumulating data has shown important exceptions to these general rules, in particular, the description of CD8+ T cells restricted by MHC-II [2] and MHC-E [3]. Of these observations, the most dramatic is the finding that a modified RhCMV vector strain (68-1) exclusively elicits, in Rhesus macaques, broadly targeted CD8+ T cells that are restricted by either MHC-II or MHC-E, but not MHC-Ia [4,5••].…”
Section: Introductionmentioning
confidence: 99%
“…At times, genetic differences alone may be sufficient to effectively categorize cells (for example, drug-responsive versus unresponsive cancer cell clones 68,69 or which T cells will be antigen specific 70 ); in other instances (for example, distinguishing which isogenetic dendritic cells will respond in a particular way to pathogen exposure 3 ), it may be the accessibility or modifications of the genome that are relevant 71,72 . Accordingly, there has also been substantial interest in understanding how genomic structure informs cellular phenotype, as well as how it is established and maintained.…”
Section: Microfluidic Devices For the Omicsmentioning
confidence: 99%
“…A new study by Ranasinghe et al (2016) shows that virus-specific class-II-restricted CD8 + T cells can be found in some HIV-infected patients. …”
mentioning
confidence: 99%